2009
DOI: 10.1080/87565640902801882
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and Visual Processing in Children With Dyslexia

Abstract: This study investigated the temporal stability and longitudinal replicability of visual and auditory sensory processes found to be poor in children with dyslexia. Seventy children with dyslexia and 52 normal readers were tested twice, 9 months apart, on measures of visual and auditory sensory processing and on phonological and orthographic skills. About 30% of children with dyslexia were found to have sensory deficits. Associations were found between sensory and cognitive skills. Based on analyses of agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 101 publications
3
43
0
Order By: Relevance
“…Pb exposure is also associated with deficits in central auditory temporal processing (Finkelstein et al, 1998; Lurie et al, 2006; Jones et al, 2008). Of significance to the current study, children with either dyslexia or ADHD have also been shown to have deficits in auditory temporal processing (Breier et al, 2003; Facoetti et al, 2003; Putter-Katz et al, 2005; Wright and Conlon, 2009; Jafari et al, 2015). …”
Section: 1 Introductionmentioning
confidence: 78%
“…Pb exposure is also associated with deficits in central auditory temporal processing (Finkelstein et al, 1998; Lurie et al, 2006; Jones et al, 2008). Of significance to the current study, children with either dyslexia or ADHD have also been shown to have deficits in auditory temporal processing (Breier et al, 2003; Facoetti et al, 2003; Putter-Katz et al, 2005; Wright and Conlon, 2009; Jafari et al, 2015). …”
Section: 1 Introductionmentioning
confidence: 78%
“…Pre-reading children at familial risk for DD exhibited the disability in detecting CM, suggesting deficits in M pathway occur before reading commencement (Kevan and Pammer, 2008). The deficient CM detection was persistent and not affected by stimulus duration, dot density or practice (Talcott et al, 2000a; Conlon et al, 2009; Wright and Conlon, 2009). Slaghuis and Ryan (2006) found CM sensitivity in mixed subgroup of dyslexics was significantly lower than that in normal group, but CM sensitivity in surface and phonological DDs was not different from that in normal readers.…”
Section: Introductionmentioning
confidence: 90%
“…However, the theoretical relationship between these centers is still underexplored (Hruby et al, 2011). A more substantiated finding is that current neurological theories of reading disorders have been unable to explain that about 30% of children with reading difficulties do not respond to reading interventions that are based solely on language processing (Laycock & Crewther, 2008;Ramus, 2003;Wolf & Bowers, 1999;Wright & Conlon, 2009). …”
Section: Neuroscience Education and Psychology Perspectivesmentioning
confidence: 95%